Surrogate mother makes money by making baby: Do we need a clear law on this? / Irma Kamarudin…[et al.] - Kamarudin, Irma; Che Rose, Sarirah (Universiti Teknologi MARA, Kedah, 2011)
carry a child to maturity in her womb and is usually resorted to by well off infertile couples who can afford the cost involved in order to fulfill their dream of being parents. This procedure is legal in several countries due to high international demand. For women who are unable to conceive, this is one of the alternatives for them to have their genetic offspring. Aside from several advantages, surrogacy in fact, invites highly controversial issues. There are numerous cases where the surrogate mother has refused to hand over the child because the process of surrogacy itself involves emotional and psychological issues. Moreover, the infertile spouses will have to worry about legal complications of a contract with the surrogate mother since the consideration of ‘buying a child’ cannot create a binding contract. There is also a possibility that child‘s emotional development will be affected because of this surrogacy process. This paper will be focusing on commercial surrogacy in Malaysia; on whether it should be banned or regulated by Malaysian Law. The Writers will look at other countries’ law pertaining to this issue by taking into consideration its regulation, advantages, disadvantages, ethics and religious perspective. At the end of this discussion, the writers will come out with suggestion either commercial surrogacy should be legally allowed or banned in Malaysia.